A new family of sodium niobate-based dielectrics for electrical energy storage applications. Issue 9 (August 2019) - Yang, Zetian; Du, Hongliang; Jin, Li; Hu, Qingyuan; Qu, Shaobo; Yang, Zhaoning; Yu, Ying; Wei, Xiaoyong; Xu, Zhuo
Abstract: Although tremendous achievements have been made in enhancing recoverable energy storage density ( W rec ) of lead-free dielectric ceramics for electrical energy storage applications in recent years, these ceramics with high W rec still have two disadvantages: complex chemical composition and difficult preparation process. In this work, we selected NaNbO3 (NN)-based ceramics as base materials and used Bi2 O3 as a sintering aid to reduce porosity and enhance dielectric breakdown strengths. Encouragingly, high W rec, simple chemical composition and facile preparation process were simultaneously realized in 0.77NaNbO3 -0.23BaTiO3 (0.77NN-0.23BT) ceramics. A large W rec of 1.5 J cm −3 at 175 kV cm −1 and excellent thermal stability (variation of W rec < 15% over the temperature range of 20˜140 °C) were simultaneously achieved in 0.77NN-0.23BT ceramics. More importantly, this work could bring out the development of a series of NN-based ceramics for electrical energy storage in the future such as NN-ABO3 (A = Ca and Sr; B = Ti and Zr).